1978
DOI: 10.1017/s0305000900001963
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and sequential constraints on six-year-olds' phonological productions: some observations on the ‘ambliance’ phenomenon

Abstract: This paper reports the results of a preliminary study dealing with the ways in which children between six and seven years of age organize spoken language. In particular it deals with aspects of the temporal and segmental structure of polysyllabic English words containing the syllable C/jul/ (e.g. pediculous). On the basis of data presented, it is suggested (a) that in order to meet certain phonological conditions it is the relations between syllable (and not segment) durations which must undergo modification t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The SPLITTING process in consonant cluster production, characterized by insertion of a schwa between two consonants, suggested by Kornfeld (1971a, b) and observed by Gilbert & Johnson (1978), can be considered in this interpretation as an attempt to overcome the demands of a timing-dominant system; the child's timing control is not developed enough to enable him to produce the required segments within the limited time allowed. Consequently, the segmentation of clustered features is exaggerated in the split clusters, allowing target articulation of consonants to be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SPLITTING process in consonant cluster production, characterized by insertion of a schwa between two consonants, suggested by Kornfeld (1971a, b) and observed by Gilbert & Johnson (1978), can be considered in this interpretation as an attempt to overcome the demands of a timing-dominant system; the child's timing control is not developed enough to enable him to produce the required segments within the limited time allowed. Consequently, the segmentation of clustered features is exaggerated in the split clusters, allowing target articulation of consonants to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into acquisition of consonant clusters in children's speech, while often noting processes indicative of reorganization of cluster features into single rather than multiple segments (Templin 1957, Kornfeld 1971a, b, Menyuk & Klatt 1968, Menyuk 1972, Gilbert & Johnson 1978, have not generally considered these processes in terms of temporal organization of speech. Several investigations have indicated that timing control in children, in particular timing control of speech, is inferior to that of the adult (Eguchi & Hirsh 1969, Kewley-Port & Preston 1974, Menyuk & Klatt, 1975, Gilbert 1977.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of target phonemes alters according to the number of syllables in words (Ingram, Christensen, Veach and Webster, 1980 ), the nature of the sound sequences (Gilbert and Johnson, 1978) and the stress of the syllables in which the phonemes occur ( Ingram et al, 1980;Klein, 1982;Gerken, 1994;Kehoe and Stoel-Gammon, 1997 ). Most of the tests do not explicitly include these variables.…”
Section: Normal Speech Developmentmentioning
confidence: 99%
“…Gilbert and Johnson (1978 ) observed that children in the age range of 6 to 7 years had di culty imitating polysyllabic words containing the C1 / jul / sequence, in words such as ambulance and binoculars, despite having demonstrate d the ability to successfully articulate each of these sounds in other sequences. Such an observation demonstrate s both the independence and interdependence of segments.…”
Section: Normal Speech Developmentmentioning
confidence: 99%